An Overview of the Oscillating Water Column (OWC) Technologies: Issues and Challenges - Khaleghi, Sadegh; Lie, Tek Tjing; Baguley, Craig (Journal of Basic & Applied Sciences, 2022)
There is a vast amount of energy available in ocean waves which can contribute to provide the electricity supply specially for countries surrounded by the ocean. This paper provides background knowledge in different techniques to harness the kinetic and potential energy in wave power along with an overview of the recent developments in Oscillating Water Columns Wave Energy Converters. The main purpose of this study is to provide a thorough review on the current state of the technology and methods in Wave Energy Converters and to help scientists to find the future potential and gaps in this area. Moreover, significant research opportunities are identified based on the literature review of the existing research studies, and research problems to be addressed are presented and can be used as tool for the future research in this area.